Post-traumatic Stress Disorder in Soldiers Returning from Vietnam: A Survey on the Psychological Disorder of Veterans - Marios, Daskalopoulos; Ioannis, Tagarakis A.; Fani, Tsolaki; Dikeos, C; Oikonomopoulou, C.; Georgios, Tagarakis I. (Advances in Social Sciences Research Journal, 2024)
The present research aims to analyze and provide information about a very important disorder, post-traumatic stress disorder or PTSD. Then, what specifically refers to the existence of PTSD and soldiers returning from the Vietnam War who are exposed to the severely traumatic event that is combat and all that it brings with it. This empathy has led them to anxiety, overstimulation, depression and other such traumatic intense emotions. First, the evidence-based scientific term PTSD is analyzed in terms of etiology, complexes, factors and treatment. It then refers to and gives an in-depth look at the Vietnam War and how it developed the phenomena of post-traumatic stress disorder. In addition, more information about PTSD is given. Aim: The aim of this dissertation is to analyze and present the topic of Post-Traumatic Stress Disorder of the Vietnam Veterans and the way they were treated with their homecoming in the United States of America through a literature review. More specifically, the post-traumatic stress disorder due to psycho-trauma and the psychosocial effects are analyzed. Purpose: The main goal of this dissertation is the comprehensive analysis of this particular disorder and the investigation of this specific war era. Method and materials: The methodology included a collection of information on the subject from articles and books of the last decade in the Pubmed database and the Hellenic Academic Libraries Association (HEAL-Link). In conclusion, Post-Traumatic Stress Disorder is a more common phenomenon than the public believes and is one of the most difficult types of disorder. People who carry it and suffer daily, need help both from the familiar family environment and from the social environment. Therefore, it is extremely important to know the disorder and to be fully understood by experts in dealing with it, but also by people in the social environment around us, as their attitude towards the phenomenon is almost catalytic.